The Contribution of Islamic Boarding Schools In Advancing Islamic Education In Indonesia (Case Study of Al Huda Islamic Boarding School Gorontalo) - Hasyim Mahmud Wantu; Arten Mobonggi; Abdurrahman R. Mala; Munirah Munirah; Wiwik Pratiwi (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
To further Islamic education in Indonesia, Islamic boarding schools play a crucial role. The purpose of this research is to determine the positive and negative effects that Al Huda Islamic Boarding School Gorontalo has had on the local community and to assess the role that the school has played in furthering Islamic education. The researchers used a case study methodology, gathering information via observation, interviews, and document analysis. We use qualitative methods to examine the data. The findings demonstrate the crucial role that Al Huda Islamic Boarding School Gorontalo has played in promoting the state of Islamic education. They provide a comprehensive religious education that covers the Quran, Hadith, fiqh, and aqidah. In addition, this Islamic Boarding School also promotes the development of values and morality, developing a responsible and decent moral generation. This research provides more evidence that Islamic boarding schools like Al Huda Islamic Boarding School Gorontalo in Indonesia are crucial to the development of Islamic education. They have produced a generation with strong faith, morals, and minds. This Islamic boarding school in Indonesia does more than just teach its students about Islam; it also fosters community growth and religious tolerance. When it comes to improving Islamic education and Indonesian society as a whole, Islamic boarding schools play a pivotal role.